Effect of Dietary Supplementation of Citrullus colocynthis Seeds on Performance and Carcass Yield of Broiler Chickens - Ali, Sayda A.M.; Abdalla, Hyder O.; Elameen, Mohamed D. (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted to study the effect of Citrullus colocynthis seeds on the performance of broiler chickens, using diets containing four levels of C. colocynthis seed powder (0%, 2%, 4% and 6%). Three hundred sixty males one day of age chicks (Ross strain) were randomly allotted to four treatments with three replicates. All groups were fed ad libitum from one day to 49 days of age. Data were analyzed according to the completely randomized design, and Duncan’s multiple range test was used for means comparison. Live body weight, carcass weight and dressing percentages significantly (P≤0.05) increased as the dietary level of C. colocynthis seeds increased. Feed intake, feed conversion ratio and abdominal fat pad weight significantly (P≤0.05) decreased as the dietary level of seed supplementation increased. The group fed on 6% had significantly (P ≤ 0.05) the heaviest gastrointestinal weights (empty intestine, empty gizzard) and heart and liver weights. Therefore, C. colocynthis seeds can be added to broiler feeds up to 6% without adverse effects.